App-based interventions for the prevention of postpartum depression: a systematic review and meta-analysis - Yumika Miura; Yusuke Ogawa; Ayako Shibata; Kyosuke Kamijo; Ken Joko; Takuya Aoki (BMC, 2023)
Abstract Background This study explored whether psychosocial intervention applications (apps) are effective in preventing postpartum depression. Methods We conducted an initial article search on 26 March 2020, and the updated search on 17 March 2023 on the electronic databases of the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE via Ovid, Scopus, PsycINFO, CINAHL, and ProQuest Dissertations & Theses A&I. Furthermore, we searched the International Clinical Trials Platform Search Portal (ICTRP), and Clinical Trials. Results We identified 2515 references, and sixteen studies were ultimately included in this review. We conducted a meta-analysis of two studies on the onset of postpartum depression. There were no significant differences between the intervention and control groups (RR 0.80; 95% CI 0.62 to 1.04; P = 0.570). We performed a meta-analysis of the Edinburgh Postnatal Depression Scale (EPDS). The intervention group had significantly lower EPDS scores than the control group (mean difference -0.96; 95% CI -1.44 to -0.48; P < 0.001, I2 = 82%, Chi2 = 62.75, P < 0.001; high heterogeneity). Conclusion This study presents the results of current RCTs on interventions with apps, including an app with an automated psychosocial component for preventing postpartum depression that has been conducted. These apps improved the EPDS score; furthermore, they may prevent postpartum depression.